Ethics of personality communication in an educational process - Natalia Boychenko (Cхід, 2013)
The article is devoted the exposure of philosophical principles of mutual relations of participants of educational process as a central problem of ethics of high school. Critical analysis of Lawrence Kohlberg's theory of formation of personality as the valued education, and also of Niklas Lumann's socially-system conception of teaching is carried out. The own version of comprehension of philosophical principles of mutual relations of participants of educational process, which leans on the theory of Kohlberg and Lumann, is offered.